Progressive Character-Based Education - Nur Rohman Ustman; Yusuf Sofiyan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Progressive Character-Based Education is an innovative approach aimed at building a generation that is not only academically intelligent but also moral and virtuous. The background, problem formulation, and research objectives regarding progressive character-based education in Indonesia are discussed in this article. This article contributes significantly to the implementation of character education in schools, based on data from the National Education Standards Agency (BSNP) and the Ministry of Education and Culture of the Republic of Indonesia. The purpose of this study is to explore insights into progressive character-based education, examine how it is applied, and provide recommendations for improving education in a better and more sustainable way. Progressive character-based education is expected to shape individuals who possess not only knowledge but also positive behavior and attitudes in daily life. This will be achieved through a comprehensive and innovative approach